Chimpanzee diet and habitat selection in the Budongo Forest Reserve, Uganda - Tweheyo, Mnason; Lyeb, Kare A.; Weladji, Robert B. (Forest Ecology and Management, 2004)
Between June 2000 and August 2001 observations were made on food types, plant species and parts consumed by chimpanzee in relation to various habitats in the Budongo Forest Reserve (BFR), Uganda. Factors influencing their occurrence as well as their activity patterns were also assessed. The chimpanzees of the BFR spent 80% of their daytime feeding and their diet comprised 56 plants species of which 94% were trees. Chimpanzees spent most of their feeding time on B. papyrifera, Ficus sur, Ficus mucuso, Ficus exasperata and Ficus variifolia. Chimpanzees fed mostly on fruits (71%), favouring ripe ones, and young leaves (16%). Factors positively influencing occurrence of chimpanzees included habitat types (logged area and forest edge), plant types (trees), food types (fruits), fruit maturity (ripe fruits), and fruit quantity. Logged area and forest edge provided 76% of the chimpanzee food but are also the habitats with the highest human interference, e.g. logging and agriculture encroachment. Past forest management plans did not consider chimpanzee food trees; most were considered weeds and killed with aboricides. We conclude that the long-term survival of chimpanzees of the BFR requires implementation of management plans based on conservation of food tree species.
Keywords: Chimpanzees (Pan troglodytes); Feeding habits; Budongo Forest Reserve; Human disturbance; Uganda